Herder, Postcolonial Theory and the Antinomy of Universal Reason. (12th February 2014) - Noyes, John K.
<x content-type="archive" xml:space="preserve">Abstract</x> The writings of Johann Gottfried Herder are not only striking in their vehement opposition to European imperialism. They arguably present the first attempt to ground anti-imperialism not just morally but epistemologically. Herder does this through his encounter with Kant's precritical theory, augmented by a novel philosophy of language. Herder believed philosophy needs to reformulate its aims in terms of anthropology, history, and aesthetics. In the process, he found himself facing what I am calling the antinomy of universal reason. Reason is a universal characteristic of humanity. In its expressions, however, reason is plural and diverse. This antinomy has carried through into postcolonial theory, where it presents some serious epistemological and methodological challenges. Using the examples of Dipesh Chakrabarty, Achille Mbembe, and Gayatri Spivak, I show what these challenges look like. In conclusion, I inquire into Herder's attempts to find a methodology that allows a critique of imperialism while recognizing the antinomous workings of universal reason.